Post-Golgi trafficking of rice storage proteins requires the small GTPase Rab7 activation complex MON1–CCZ1. Issue 4 (19th April 2021) - Pan, Tian; Wang, Yihua; Jing, Ruonan; Wang, Yongfei; Wei, Zhongyan; Zhang, Binglei; Lei, Cailin; Qi, Yanzhou; Wang, Fan; Bao, Xiuhao; Yan, Mengyuan; Zhang, Yu; et al.
Abstract: Protein storage vacuoles (PSVs) are unique organelles that accumulate storage proteins in plant seeds. Although morphological evidence points to the existence of multiple PSV-trafficking pathways for storage protein targeting, the molecular mechanisms that regulate these processes remain mostly unknown. Here, we report the functional characterization of the rice ( Oryza sativa ) glutelin precursor accumulation7 ( gpa7 ) mutant, which over-accumulates 57-kDa glutelin precursors in dry seeds. Cytological and immunocytochemistry studies revealed that the gpa7 mutant exhibits abnormal accumulation of storage prevacuolar compartment-like structures, accompanied by the partial mistargeting of glutelins to the extracellular space. The gpa7 mutant was altered in the CCZ1 locus, which encodes the rice homolog of Arabidopsis ( Arabidopsis thaliana ) CALCIUM CAFFEINE ZINC SENSITIVITY1a (CCZ1a) and CCZ1b. Biochemical evidence showed that rice CCZ1 interacts with MONENSIN SENSITIVITY1 (MON1) and that these proteins function together as the Rat brain 5 (Rab5) effector and the Rab7 guanine nucleotide exchange factor (GEF). Notably, loss of CCZ1 function promoted the endosomal localization of vacuolar protein sorting-associated protein 9 (VPS9), which is the GEF for Rab5 in plants. Together, our results indicate that the MON1–CCZ1 complex is involved in post-Golgi trafficking of rice storage protein through a Rab5- and Rab7-dependent pathway. Abstract : The small GTPases Rab5- and Rab7-dependent pathway is involved in rice storage protein trafficking to vacuoles.